2nd International Eindhoven LSP Conference, 3-6 August 1988 - Andersen, Birger; Laursen, Anna-Lise; Pilegaard, Morten; Trosborg, Anna (HERMES - Journal of Language and Communication in Business, 1989)
Intet abstract